UPAYA GURU BK DALAM MENGEMBANGKAN HUBUNGAN SOSIAL PESERTA DIDIK DIKLAT DI SMA NEGERI 5 PADANG - Erviana, Elvia - (Bimbingan dan Konseling, 2014)
The background of this research is less of counseling teacherâs action in developing social relationship learner training. The purpose of this research were to describe the effort of counseling teacher in: 1) developing social skill, 2) giving the opportunity for the learner to be active in group activities, 3) guiding the learner in democratic life, 4) discussing the problem of women and man social, 5) encourage the learner to read the literature about women and man, 6) assign the learner to observe the social life. Kinds of this research was descriptive quantitative. The populations were 67 people. Technique of gathering sampling was using total sampling. The instrument was questionnaire. Analysis of the data was using percentage formula. The result of this research showed counseling teacherâs effort in: 1) developing social skill are very good category, 2) giving the opportunity for the learner to be active in group activities are in good category, 3) guiding the learner in democratic life are in good category, 4) discussing the problem of women and man social are in good category, 5) encourage the learner to read the literature about women and manare in very good category, 6) ) assign the learner to observe the social life. Kinds of this research was descriptive quantitative are in very good category.